KARMA PHALA DAN PANGRUWATAN DALAM TEKS LONTAR TUTUR LEBUR GANGSA - I Made Suweta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
The teachings of Hinduism are contained in the Vedic scriptures and are applied in various literary works. The orthodoxy of the Hindu community in Bali, in understanding the teachings of the Vedas can be through the original media of the archipelago culture through lontar texts. In the life of the Balinese people, lontar get a very important place, as a source of various knowledge. The problem to be discussed in the Lontar Lebur Gangsa text is how is the law of karmaphala and pangruwatan in the text Lontar Lebur Gangsa? Based on the discussion on the text Lontar Tutur Lebur Gangsa, it can be mentioned about the human condition in this life; like why humans can experience good conditions now that are felt as a beauty, and also sometimes ugliness? According to the text Lontar Tutur Lebur Gangsa, this is nothing but the result (phala) of his own actions (Karma), which are related to Sancita, Karmaphala, Pralabdha, and Kriyamana Karmaphala, which is explained explicitly about the consequences obtained from the deeds done by humans. Everything that causes misery in human life is also associated with the ritual ruwatan as an attempt to cleanse spiritually in the hope that all deficiencies can be neutralized into a better life.Keywords: Text of Lontar Lebur Gangsa, Karma Phala, Pangruwatan